If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + 8x + -4 = 20 Reorder the terms: -4 + -2x + 8x = 20 Combine like terms: -2x + 8x = 6x -4 + 6x = 20 Solving -4 + 6x = 20 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 6x = 20 + 4 Combine like terms: -4 + 4 = 0 0 + 6x = 20 + 4 6x = 20 + 4 Combine like terms: 20 + 4 = 24 6x = 24 Divide each side by '6'. x = 4 Simplifying x = 4
| 15(t-3)+6t=7(3t+2)-10 | | -3(4b+1)+(13b-9)=0 | | 1/3m-q | | 175*29/35*6/25 | | 9r=-45 | | m+2m=18 | | 9xX-28=15 | | (-2v)-7=-23 | | 3y+9/6y | | 3y-9/6y | | (n-5)*10=100 | | 4/17x=28 | | (n-5)*4=16 | | 140-5x=6x+9 | | 7(2b-3)+2=5*15+(b-3) | | y/3=13 | | -(7y+1)-(-6y-5)=0 | | 0=2x^2+4x-11 | | 3r+12r=30 | | 3(n-2)=22 | | 2x-6=30-25x | | (n*9)-6=48 | | 2a+3b=31 | | 15s+6t=99 | | 4+16s-2=8s+24-3s | | 6x+4+x=11 | | 14/9*15/12*8/35 | | 4y-4=3x-1 | | 16(2x-4)=4(8x+7) | | 9p+6q=42 | | 10-10x=28-17x | | 2[7-(-7x-6)]=84x+86 |